2013
DOI: 10.1103/physrevc.87.065801
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear structure of30S and its implications for nucleosynthesis in classical novae

Abstract: Background:The uncertainty in the 29 P(p, γ) 30 S reaction rate over 0.1 ≤ T ≤ 1.3 GK was previously determined to span ∼4 orders of magnitude due to the uncertain location of two previously unobserved 3 + and 2 + resonances in the E x = 4.7 -4.8 MeV region in 30 S. Therefore, the abundances of silicon isotopes synthesized in novae, which are relevant for the identification of presolar grains of putative nova origin, were uncertain by a factor of 3.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 68 publications
(557 reference statements)
0
13
0
Order By: Relevance
“…The method is used for the level at 5.2 MeV, which is found to be either a 3 + or 4 + level, with the data favoring the 3 + . In previous studies this level has been suggested to be a 0 + level [12] based on a comparison with the mirror nucleus, or as a 3 + level based on its γ decay [29]. It is currently not known if there might be two levels around this energy, but we can conclude that a 3 + level at 5.227(3) MeV is populated in the decay of 31 Ar.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The method is used for the level at 5.2 MeV, which is found to be either a 3 + or 4 + level, with the data favoring the 3 + . In previous studies this level has been suggested to be a 0 + level [12] based on a comparison with the mirror nucleus, or as a 3 + level based on its γ decay [29]. It is currently not known if there might be two levels around this energy, but we can conclude that a 3 + level at 5.227(3) MeV is populated in the decay of 31 Ar.…”
Section: Discussionmentioning
confidence: 88%
“…This is only possible for the strongest fed level in 30 S at 5.2 MeV. This level has previously been assigned either as 0 + [12] based on levels in the mirror nucleus or as a 3 + state based on its γ decay [29]. To have sufficient statistics all detectors are used with a low-energy cutoff on the first particle of 800 keV and the second of 500 keV, except for the thick detector 5, where 800 keV is used.…”
Section: E Spin Of Low-lying Levels Of 30 Smentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the influence of new magic numbers N = 14, 16, the calculated deformations of these two nuclei are very small with some different mass models such as the Weizsäcker-Skyrme mass model, the finite range droplet model [38], and the HFB calculations [5] adopting three widely used Skyrme forces SLy4, SkP and SkM*. We systematically calculate the difference of the rms charge Due to the perfectly charge-symmetric and charge-independent nuclear force, the deformations and shell correction of a nucleus approximately equal to those of its mirror nucleus [25,40]. Based on the proposed nuclear charge radius formula, one obtains ∆r ch ≈ 3 5 2r s I neglecting the influence of nuclear deformations.…”
mentioning
confidence: 99%